Corporate Governance of State-Owned Enterprises in Latin America : Current Trends and Country Cases - World Bank (World Bank Group, Washington, DC, 2014)
The main objective of this report is to provide a descriptive analysis of the current practices and trends of corporate governance of State-owned Enterprises (SOEs) in several Latin-American countries. It provides practitioners of SOE corporate governance with a stocktaking of current practices and trends in several Latin American countries, as well as international experiences and good practices elsewhere. This report intend to contribute to the discussion and growing interest on SOE corporate governance and to provide an impulse for further analytical work in this area. In most Latin American and Caribbean countries, the SOE sector contributes significantly to GDP and represents an important part of consolidated public expenditures. In several cases, the SOEs are also key and strategic actors in the country s economy providing essential goods and services and frequently hold a dominant market position in critical sectors, such as petroleum, electricity, and transportation. They also operate in competitive markets such as financial services, telecommunications, etc. SOEs are also increasingly under pressure, by both their governments and by international competition, to operate and achieve their goals more efficiently and effectively. Within this context, achieving good corporate governance practices is critical to SOEs effectively providing goods and services and achieving their short-, medium-, and long-term goals, within a sustainable fiscal framework. This report has been prepared with the direct collaboration of government officials involved in the SOE sectors of eight countries in Latin America and the Caribbean, and Spain. It is mainly based on financial information and other relevant data on the above-mentioned countries, covering the period from 2010 to 2013. As part of data collection for the report, representatives of the SOE sectors in Brazil, Chile, Colombia, Dominican Republic, Mexico, Panama, Paraguay, Peru, Spain and Uruguay, attended the Technical Workshop on SOE Supervision in Latin American and Caribbean Countries, organized by the SOE Monitoring Unit of Paraguay and the World Bank in December 2011 in Punta del Este, Uruguay.